2022
DOI: 10.1093/advances/nmab162
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prunes in Modulating Inflammatory Pathways to Improve Bone Health in Postmenopausal Women

Abstract: The prevalence of osteoporosis among women aged 50 years and older is expected to reach 13.6 million by 2030. Alternative non-pharmaceutical agents for osteoporosis including nutritional interventions are becoming increasingly popular. Prunes (dried plums) (Prunus domestica L.) have been studied as a potential whole food dietary intervention to mitigate bone loss in preclinical models of osteoporosis and in osteopenic postmenopausal women. Sixteen preclinical studies using in vivo rodent models of osteopenia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 176 publications
0
19
0
Order By: Relevance
“…Flow cytometric analysis: Phenolic compounds in prunes are reported to have numerous anti-inflammatory and anti-oxidative effects [ 35 ]. We chose to assess the effect of prunes on the number and activation status of monocytes as they are one of the main producers of inflammatory cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometric analysis: Phenolic compounds in prunes are reported to have numerous anti-inflammatory and anti-oxidative effects [ 35 ]. We chose to assess the effect of prunes on the number and activation status of monocytes as they are one of the main producers of inflammatory cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown GM and VM regulates inflammation (9,23,(33)(34)(35), which is related to osteoporosis, so we hypothesized that osteoporosis may be associated with an increase in systemic inflammation by GM and VM. The results in this study showed that the level of the anti-inflammatory factor IL-10 was significantly lower in the osteoporosis group than in the control and osteopenia groups (Figure 5A).…”
Section: Changes In Systemic Inflammationmentioning
confidence: 98%
“…In addition to prunes, other polyphenol-rich foods exhibit similar biological activity in the prevention of bone loss (Lucas et al, 2020). Future research should aim to investigate whether this protective effect is associated with alterations in gut microbes (Damani et al, 2022). Foods rich in anthocyanins, calcium, unsaturated fatty acids, bioactive peptides, and polyphenols regulate the diversity and composition of the intestinal microbiota to a certain extent and thus have a beneficial effect on the bone.…”
Section: Dietmentioning
confidence: 99%
“…In addition to prunes, other polyphenol-rich foods exhibit similar biological activity in the prevention of bone loss ( Lucas et al., 2020 ). Future research should aim to investigate whether this protective effect is associated with alterations in gut microbes ( Damani et al., 2022 ).…”
Section: Interventions With Specific Gut Microbiota To Improve Bone H...mentioning
confidence: 99%